Children's recognition of slapstick humor is linked to their Theory of Mind - Ger, Ebru; Daum, Moritz M.; Manfredi, Mirella (Frontiers in Cognition, 2024)
Humor is an important component of children's learning and development. Yet, the cognitive mechanisms that underlie humor recognition in children have not been well-researched. In this preregistered study, we asked whether 1) 4-to 5-year-old children recognize and categorize a misfortunate situation as funny only if the victims show a funny bewildered face (slapstick humor), and not a painful or angry expression, 2) this ability increases with age, 3) it is associated with children's Theory of Mind (ToM) abilities, 4) it is related to the ability to recognize facial emotional expressions. In an online experiment platform, children (N = 61, Mage = 53 months) were asked to point to the funny picture between a funny and an affective picture. Then, children were asked to point to the happy, sad, fearful, or angry face among four faces displaying these emotions. Children's ToM was assessed using the Children's Social Understanding Scale (CSUS; Tahiroglu et al., 2014), which was filled out online by parents. Results showed that from the earliest age onward, the predicted probability of humor recognition exceeded the chance level. Only ToM but not age was a significant predictor. Children with higher ToM scores showed better humor recognition. We found no evidence for a relation between children's humor recognition and their recognition of any emotion (happy, sad, fearful, or angry). Our findings suggest that 4-to 5-year-old children recognize facial emotional expressions and slapstick humor, although these abilities seem unrelated. Instead, children's understanding of mental states appears to play a role in their recognition of slapstick humor.